(untitled) (Bangladesh Journal of Zoology, 2015)
An investigation was carried out on the proximate and mineral contents of widely consumed freshwater small indigenous species (SIS), culture and marine fish species of Bangladesh. Proximate composition (crude protein, fat, ash, moisture, carbohydrate and energy) and selected mineral (Ca, K, Na, Mg, Fe, Zn and Mn) contents were determined eighteen locally available fish species of Bangladesh. Considering proximate composition high protein fishes are Thai Sarpunti 17.5 ± 0.15%, Rui 16.82% ± 0.02; high fat fishes are Thai Pangus 10.03±0.1%, Thai Sarpunti 9.38±0.37%; high Ash contents in Poa 4.78 ± 0.92 %, Ganges Chapila 3.96 ± 0.51%, Thai Sarpunti 3.31 ± 0.14%; high energy found in Thai Sarpunti 157.02 ± 2.61 Kcal/g and Thai Pangus 151.59 ± 2.71 Kcal/g. Considering mineral compositions, Ca rich fishes are Punti 1984.32 ± 1.1 mg, Mola 1267 ± 2.2 mg, Dhela 1717.8 ± 3.1 mg, Chapila 1100.6 ± 1.21 mg, Thai Sarpunti 1373.9 ± 5.32 mg. K rich fishes are Taki 501.47 ± 2.9 mg, Coral 415.24 ± 2.8 mg and Na rich fishes are Thai Sarpunti 780.01 ± 3.8, Ganges Chapila 415.32 ± 2.34 mg, Loitta 497.38 ± 4.21 mg. Trace mineral, Mg is high in Coral 187.98 ± 0.61 mg, Punti 148.16 ± 0.62 mg, Datina 144.05 ± 0.35 mg, Kachki 143.49 ± 0.3 mg fishes, whereas Fe are high in Chapila 15.95 ± 0.03mg, Punti 10.31 ± 0.2, Poa 7.01±0.66 and Zn in Thai Sarpunti 40.20 ± 0.34 mg, Poa 29.32 ± 0.32 mg fishes. Considering Mn, Chapila 6.34 ± 0.04 mg is the highest. This study indicate that small fishes with bones are important source of essential minerals especially Ca. Culture species found to be rich in source of protein, energy and lipids. Marine species exhibit good combination of protein and minerals. This study also encourage to take a culture species like Thai Sarpunti (Barbonymus gonionotus) for its high nutritional meat values and also to consume marine fishes and small fishes with bones for better nourishment. Promotion of the production and consumption of small fishes therefore be encouraged for better nutritional achievement. Bangladesh J. Zool. 42(2): 251-259, 2014